The Moral Sensitivity of Students Through The Meaningfull Learning Model on Natural Science Subjects in Secondary School - Nita Lailatul Fauzia; Septi Budi Sartika (International Consortium of Education and Culture Research Studies, 2020)
The study aims to describe the moral sensitivity of students by applying a meaningfull learning model of use in the topic of global warming in secondary school. Research methods use descriptive quantitative research, with pre-experimental design. The data retrieval technique uses Pre-Test and Post-test of moral sensitivity tests. The meaningfull learning model of packaging in secondary school can increase the moral sensitivity of students with N-Gain score of 0.31 which means there is an increase in the medium category, it is also supported by the implementation of learning with good average and the relevant student activity during the learning process. The learning model of the method has 7 syntax, where the use of moral sensitivity is in 6th syntax which is the syntax of usage. In this syntax the concept of natural science is interpreted by associating moral values. Further studies are expected to increase the moral sensitivity of students with high category, so that the learning model of the method is undoubtedly the excess.